ANALISIS KINERJA KARYAWAN DALAM PENCAPAIAN KEPUASAN KONSUMEN PADA KOPERASI MITRA DUTA PONTIANAK - Lastari, Desy; Khosmas, Khosmas; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrakhis thesis is entitled, "Analysis of Employee Performance in Achieving Consumer Satisfaction in the Pontianak Partnership Ambassador" Partnership Ambassador Cooperative" as for the sub-problems are 1) What is the employee's performance of the Quality factor Of Work (Work Quality) in achieving customer satisfaction in the Pontianak Partnership Duta Cooperative ?, 2) What is the employee's performance from the Quantity of Work factor in achieving customer satisfaction in the Pontianak Partnership Ambassador? 3) What is the employee's performance of the Timeliness factor (time determination) in achieving customer satisfaction in the Pontianak Partnership Ambassador ?. The method used in this study is a descriptive method with a survey research form.. The results of this study are (1) employee performance seen from the aspect of quality (quality) both from employee services, employee responsibilities and employee performance skills are good. (2) Employee performance can be seen from the Quantity aspect (quantity) both from the responsiveness of the management and the performance capabilities of the management are good. (3) Employee performance is inspired by the aspect of timeliness (time determination) when processing loans, and the ease of service is good, members and consumers judge employees on time in serving members. Keywords: Employee performance, Consumer satisfaction, Cooperatives